2018
DOI: 10.1016/j.ebiom.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Fats Inhibit Autophagy Induced by Saturated Fatty Acids

Abstract: Depending on the length of their carbon backbone and their saturation status, natural fatty acids have rather distinct biological effects. Thus, longevity of model organisms is increased by extra supply of the most abundant natural cis-unsaturated fatty acid, oleic acid, but not by that of the most abundant saturated fatty acid, palmitic acid. Here, we systematically compared the capacity of different saturated, cis-unsaturated and alien (industrial or ruminant) trans-unsaturated fatty acids to provoke cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Oleate supplementation was shown to extend the life span of flies and worms (72, 73). Moreover, previous studies have revealed Acc1 to be required for dietary restriction-induced longevity and starvation resistance in Drosophila melanogaster (74).…”
Section: Discussionmentioning
confidence: 99%
“…Oleate supplementation was shown to extend the life span of flies and worms (72, 73). Moreover, previous studies have revealed Acc1 to be required for dietary restriction-induced longevity and starvation resistance in Drosophila melanogaster (74).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the synthetic pathway of mono-unsaturated fatty acids also contributes to autophagy. Finally, a recent study has shown that trans-unsaturated fatty acids inhibit autophagy induced by saturated fatty acids 220 , implying complicated connections between autophagic effects caused by different types of fatty acids. Further analyses are needed to elucidate how individual fatty acids act on autophagy.…”
Section: Emerging Roles Of Lipid Metabolism In Autophagosome Biogenesismentioning
confidence: 99%
“…GFP-LC3 dot area was measured by ImageJ. acids 22 for their capacity to induce the formation of autophagic puncta in human H4 neuroblastoma cells that express a green fluorescent protein (GFP) fused to microtubule-associated proteins 1A/1B light chain 3B (best known as LC3) ( figure 1A,B; online supplementary table S1). The 175 compounds that were most efficient at one of the chosen concentrations were re-tested on another cell line, namely, human U2OS osteosarcoma cells stably expressing the monomeric S3).…”
Section: Autophagy Measurement On Tissue Sectionsmentioning
confidence: 99%